Розвиток соціально-психологічних методів управління персоналом в умовах воєнного стану - Пшик-Ковальська, О. О.; Ковальський, О. І.; Phsyk-Kovalska, O. O.; Kovalskiy, O. I. (Видавництво Львівської політехніки, 2023)
Стаття присвячена актуальним питанням впливу на працівників в умовах воєнного стану. На основі узагальнення основних теоретичних підходів обґрунтовано точку зору щодо важливості посилення адаптації персоналу до нових умов діяльності, формування низки заходів з метою утримання професійних кадрів та недопущення їх емоційного вигорання. Було обґрунтовано доцільність застосування керівником соціально-психологічних методів менеджменту. Аргументовано необхідність формування в умовах воєнного стану у працівників психологічних ресурсів. Практична значущість статті полягає в тому, що на базі аналізу літературних джерел щодо існуючих способів соціальних і психологічних впливів ідентифіковано напрямки формування психологічних ресурсів у працівників.

Personnel management is an activity that creates many new challenges for managers who implement it at the enterprise. Today, one of these challenges is personnel management under martial law. In the conditions of martial law, a person’s mental state is especially vulnerable, which is accompanied by a change in behavior, a low level of information perception, and an aggressive attitude towards others. All these negative processes are formed under the influence of stress in which people are, in particular, employees in organizations under martial law. People perceive and experience stress in different ways, some gradually adapt to the new reality, recover, and some in response to stressful circumstances and events feel uplifted and want to move forward against everything. In the conditions of martial law, the mental health of employees is a factor that significantly affects labor productivity. Therefore, there is a need for the manager to use social and psychological methods at all levels and stages of management. This will contribute to the formation of a highly qualified and effective team, each member of which will realize their potential at the highest level, as a result of which the efficiency of the enterprise will in crease. Social-psychological methods appeal to the management of relationships. The main specificity of such methods is the use of informal factors, interests of the group, collective. At the same time, the competently implemented socio-psychological influence of the manager will form the employee’s psychological resources for long-term successful activity. The main feature of psychological methods is the appeal to the inner world of a person, his personality, intelligence, feelings, images and behavior in order to direct the inner potential of a person to the solution of specific tasks of the enterprise. A review of literary sources and own research allow us to state that the formation of an effective labor team in the conditions of martial law directly depends on the identification, formation and development of psychological resources among employees. Despite the difficult operating conditions of domestic enterprises, the proposed directions for the formation of psychological resources and well-argued evidence of the effectiveness of socio-psychological personnel management methods in the conditions of martial law should comprehensively solve the problem of reducing labor productivity, namely, from reducing organizational stress to improving the company’s reputation, increasing trust in leadership and team cohesion.
Development of social-psychological methods of personnel management under the conditions of martial law
Keywords: психологічний ресурс; методи управління персоналом в умовах воєнного стану; методи соціального впливу; методи психологічного впливу; стрес; psychological resource; methods of personnel management in conditions of martial law; methods of social influence; methods of psychological influence; stress; 658.3; 005.95/.96